2009
DOI: 10.2172/962428
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Reproductive Success of Naturally Spawning Hatchery and Natural Spring Chinook Salmon in the Wenatchee River, 2008-2009 Progress Report.

Abstract: Executive SummaryWe investigated differences in the statistical power to assign parentage between an artificially propagated and wild salmon population. The propagated fish were derived from the wild population, and are used to supplement its abundance. Levels of genetic variation were similar between the propagated and wild groups at 11 microsatellite loci, and exclusion probabilities were >0.999999 for both groups. The ability to unambiguously identify a pair of parents for each sampled progeny was much lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…In contrast, and similar to the coho salmon study, we found little evidence that the use of wild origin fish as broodstock influenced the reproductive success of their progeny. This observation appears consistent with the observed high rates of exchange between the hatchery and natural environments in our study population (Ford et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, and similar to the coho salmon study, we found little evidence that the use of wild origin fish as broodstock influenced the reproductive success of their progeny. This observation appears consistent with the observed high rates of exchange between the hatchery and natural environments in our study population (Ford et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…A hatchery program was established on the Chiwawa River, a major spring-run Chinook spawning tributary of the Wenatchee River, in 1989 to supplement the wild population; this hatchery uses a mixture of natural and hatchery origin fish captured within the watershed each year for broodstock. Similarly, approximately 50%-80% of the natural spawners in a given year are hatchery-origin fish (Ford et al 2013). The high rates of exchange between the hatchery broodstock and the natural spawning population make this an ‘integrated’ hatchery program with the goal of minimizing genetic divergence between the hatchery and natural groups (Mobrand et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Since 1989, hatchery supplementation using broodstock captured within the watershed has been used to increase abundance, and the hatchery has produced 50-80% of the spawners in the river each year (Ford et al 2013). Here, a hatchery-origin fish refers to a fish whose parents were spawned in the hatchery, and a natural-origin fish refers to a fish whose parents spawned in the stream, regardless of their prior ancestry.…”
Section: Study Populationmentioning
confidence: 99%